EVALUATION OF RESERVOIR WATER QUALITY USING WATER QUALITY INDEX IN GOVIND BALLABH PANT SAGAR RESERVOIR, INDIA - Ramita Varshney; Aarif Jamal (Rasayan Journal of Chemistry, c/o Dr. Pratima Sharma, 2018)
Weighted Arithmetic Water Quality Index is a single number that expresses the water quality of a sample collected from a water body by amalgamating thirteen water quality parameters in this study. The sole of this is to express the quality of water in a simple and concise manner for recreational use such as irrigation, domestic or industrial. This paper employs Weighted Arithmetic Water Quality Index, as a simple pollution indicator tool in Govind Vallabh Pant Sagar Reservoir. The index was applied to six sampling locations and compared to each other. The quality of water was investigated for two seasons of the year i.e. pre and post-monsoon seasons. The results showed that the water quality during both the seasons was poor thereby necessitating proper treatment before it can be used for fulfilling potable requirements.
Keywords: Water Quality Index, Reservoir water, Physico-chemical parameters, Weighted Arithmetic Water Quality Index Method